Timeless–Tipin interactions with MCM and RPA mediate DNA replication stress response - Prorok, Paulina; Wolf, Eva; Cardoso, M. Cristina (Frontiers in Cell and Developmental Biology, 2024)
The accuracy of replication is one of the most important mechanisms ensuring stability of the genome. The fork protection complex prevents premature replisome stalling and/or premature disassembly upon stress. Here, we characterize the Timeless-Tipin complex, a component of the fork protection complex. We used microscopy approaches including colocalization analysis and proximity ligation assay to investigate the spatial localization of the complex during ongoing replication in human cells. Taking advantage of the replication stress induction and the ensuing polymerase-helicase decoupling, we characterized the Timeless-Tipin localization within the replisome. Replication stress was induced using hydroxyurea (HU) and aphidicolin (APH). While HU depletes the substrate for DNA synthesis, APH binds directly inside the catalytic pocket of DNA polymerase and inhibits its activity. Our data revealed that the Timeless-Tipin complex, independently of the stress, remains bound on chromatin upon stress induction and progresses together with the replicative helicase. This is accompanied by the spatial dissociation of the complex from the blocked replication machinery. Additionally, after stress induction, Timeless interaction with RPA, which continuously accumulates on ssDNA, was increased. Taken together, the Timeless-Tipin complex acts as an universal guardian of the mammalian replisome, in an unperturbed S phase progression as well as during replication stress.